(3ScQOGf ehdGfG GdSdWGfs - (3CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, GHf CHj MLdg , TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3GdLjRI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfWb GdWjQ HMceJg , hCLQi GdHMGQ GdSHYI HbOQJg hHYO adeG cGfJ GdSHYI ef CTQa GdCYOGO , hcGf hLhOgG HeUQ CcKQ ef SGFQ GdHdGO CdaJ (B( (3YfgG (B) (3ai gPG GdcJGH s
(3BNQgG (B:s
(3eG EMeQ Tab GdCUjd , hOH ShGO YGQVg GdCSeQ HNOg GdCSjd h GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B201 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B113s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B994s
Keywords: (3GdJGQjNs